Implementasi GAP (Good Agriculture Practice) Lada dan Pengaruhnya Terhadap Produktivitas Lada di Desa Petaling Banjar, Kecamatan Mendo Barat - Setiawan, Fahri; Inonu, Ismed; Sitorus, Rostiar (Universitas Bangka Belitung, 2015)
Indonesia is the second pepper producing country in the world, instead of Vietnam. Bangka Belitung as one of pepper producing area in Indonesia has to increase qualityÂ and quantity through Good Agriculture Practice (GAP). Petaling Banjar is one of village which apply GAP system. This research aimed to identify condition of implemenation GAP of pepper in Pataling Barat Village, pepper producitvity, and to analyze the effect of GAP implementation to pepper productivity in Petaling Banjar village. The method used survey to 36 farmers as sample. Data analysis used Double Linear Regression, F-test and T-test. The results showed that land selection and harvest and post-harvest handling variables are in âwellâ categories. Water management and seed planting variables are in âgoodâ category. Cultivation and pest and disease control management variables are in âenoughâ category. Generally, GAP implemented by farmers in Petaling Banjar village categorized to âGoodâ. Pepper production rate is 0,5 kg/plant and pepper productivity is 798,85 kg/ha. Based on F-test, GAP of pepper gives significant effect to pepper productivity. T-test showed that seed planting gives significant effect to pepper production. Double linear regression test showed that seed planting increase pepper productivity highly with partial-coeficient regression value is 1,503, land selection is 1,068, cultivation is 0,956, water management is 0,737, soil management is 0,279, harvest and post-harvest is 0,214, and pest and disease control management is 0,044.